Transthyretin as a Novel Biomarker for Diagnosis of Hepatocellular Carcinoma in Cirrhotic Patients - Magda Ibrahim (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Hepatocellular carcinoma [HCC] is one of the leading causes of cancer-related deaths worldwide. A major problem with HCC surveillance is the lack of reliable biomarkers. Serum transthyretin [TTR] may be a sensitive marker for the diagnosis of patients with liver cell damage, liver cirrhosis or hepatocellular carcinoma.  Aim of the work: This study aimed to evaluate the potentiality of serum transthyretin [TTR] as a novel biomarker for detection of HCC in cirrhotic patients. Patients and Methods:This Current study was conducted on 70 patients with chronic liver disease. Also, 20 healthy person matched for age and sex were included as a control group. Patients were classified into 2 groups [30 cirrhotic patients with newly diagnosed HCC & 40 cirrhotic patients without HCC]. Serum TTR levels were measured using enzyme linked immunosorbent assay technique. Results: Serum levels of TTR were significantly much lower in HCC patients when compared to cirrhotic patients without HCC or control group [p<0.0001]. Significant decrease of serum TTR in HCC patients, with portal vein invasion or nodal invasion than in HCC without vascular or nodal invasion. The diagnostic accuracy of TTR was higher than that of AFP regarding sensitivity [83.3%] and negative predictive value [81.4%] in diagnosis of HCC. Conclusion: detection of lower level of TTR alone or in combination with other validated markers may be potentially informative biomarker for detection of HCC among cirrhotic patients at early noninvasive stage where curative treatment can be applied.